Hierarchically tubular architectures composed of vertical carbon nanosheets embedded with oxygen-vacancy enriched hollow Co3O4 nanoparticles for improved energy storage. (1st October 2020) - Gong, Yujiao; An, Jianing; Dai, Henghan; Chen, Ruyi; Yu, Chenyang; Chen, Qiang; Zhou, Jinyuan; Sun, Gengzhi; Huang, Wei
Abstract: Although great efforts have been devoted to exploiting electrode materials with designed composition and nanostructure for high-performance electrochemical energy storage devices, it remains critically challenging to achieve hierarchically tubular architectures constructed with different low-dimensional building blocks due to the lack of appropriate synthetic strategies. Herein, hierarchically tubular structures composed of vertically aligned carbon nanosheets embedded with oxygen-vacancy enriched hollow Co3 O4 nanoparticles (H-Co3 O4 /C) are prepared. Benefited from these unique features, H-Co3 O4 /C electrode containing 54 wt.% carbon and 46 wt.% Co3 O4 exhibits high specific capacity of 328.0 C g −1 at 1 A g −1, good rate capability with 70% capacity retained at 20 A g −1, improved energy density of 8.3 Wh kg −1 at the power density of 4268.5 W kg −1 as well as remarkable stability for 10, 000 charge-discharge cycles.